Antrodia cinnamomea polysaccharide improves liver antioxidant, anti-inflammatory capacity, and cecal flora structure of slow-growing broiler breeds challenged with lipopolysaccharide - Ye, Jinling; Zhang, Chang; Fan, Qiuli; Lin, Xiajing; Wang, Yibing; Azzam, Mahmoud; Alhotan, Rashed; Alqhtani, Abdulmohsen; Jiang, Shouqun (Frontiers in Veterinary Science, 2022)
Lipopolysaccharides (LPS) induces liver inflammatory response by activating the TLR4/NF-κB signaling pathway. Antrodia cinnamomea polysaccharide (ACP) is a medicinal mushroom that can protect from intoxication, liver injury, and inflammation. Nevertheless, the effect of ACP on the liver antioxidant, anti-inflammatory capacity and cecal flora structure of LPS-challenged broilers remains unclear. The aim of this experiment was to investigate the effects of ACP on the anti-oxidative and anti-inflammatory capacities of the liver, and cecal microbiota in slow-growing broilers stimulated by LPS. A total of 750 slow-growing broilers (9-day-old) were assigned to five treatments with 6 replicates of 25 chicks per replicate: a control diet, the chicks were fed a control diet and challenged with LPS. Dietary treatments 3 to 5 were the control diet supplemented with 100, 200, 400 mg/kg ACP challenged with LPS, respectively. The groups of 100 mg/kg ACP supplementation significantly increased liver index, pancreas index, and bursa of Fabricius index (P < 0.05). The GSH-Px content of LPS-challenged broilers was lower than that of the control group (P < 0.001), but the content of MDA increased (P < 0.001). Feeding with 100 mg/kg ACP resulted in increased the activity of T-AOC, GSH-Px, and T-SOD, and decreased MDA content (P < 0.05). The activity of TNF-α, IL-1β, and IL-6 of the LPS group increased, but these indicators were decreased with supplemental 100 mg/kg ACP (P < 0.05). Dietary application of ACP up to 100 mg/kg down-regulated (P < 0.05) the expression of TLR4/NF-κB pathway in the liver induced by LPS. The results of 16S rRNA demonstrated that feeding with 100 mg/kg ACP can change the diversity and composition of the gut microbiota, and restrained the decline of beneficial cecal microbiota (typically Lactobacillus, Faecalibacterium, and Christensenellaceae R-7 group) in the challenged LPS group (P < 0.05). Conclusively, feeding a diet with 100 mg/kg ACP may have beneficial effects on liver damage and the bacterial microbiota diversity and composition in the ceca of LPS-stressed slow-growing broiler breeds, probably because of its combined favorable effects on antioxidants and cytokines contents, and restoration the decline of beneficial cecal microbiota.